2021
DOI: 10.1038/s41420-021-00547-4
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of neuronal mitochondrial function by l-DOPA in the absence of oxygen-dependent auto-oxidation and oxidative cell damage

Abstract: L-3,4-Dihydroxyphenylalanin (l-DOPA or levodopa) is currently the most used drug to treat symptoms of Parkinson’s disease (PD). After crossing the blood–brain barrier, it is enzymatically converted to dopamine by neuronal cells and restores depleted endogenous neurotransmitter levels. l-DOPA is prone to auto-oxidation and reactive intermediates of its degradation including reactive oxygen species (ROS) have been implicated in cellular damage. In this study, we investigated how oxygen tension effects l-DOPA sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Recent studies have also shown that even oxygen tension affects LD stability. Under normoxic conditions, the analyte is prone to auto-oxidation by releasing protons and reactive oxygen species (ROS) as intermediates [ 33 , 34 ]. In acidic conditions, protons supplied by solvents would shift the auto-oxidation reaction equilibrium towards the reagents and avoid the formation of intermolecular bonding networks [ 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that even oxygen tension affects LD stability. Under normoxic conditions, the analyte is prone to auto-oxidation by releasing protons and reactive oxygen species (ROS) as intermediates [ 33 , 34 ]. In acidic conditions, protons supplied by solvents would shift the auto-oxidation reaction equilibrium towards the reagents and avoid the formation of intermolecular bonding networks [ 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, LD is unstable in aqueous solutions and naturally degrades over time [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]: for this reason, it is crucial to identify the best conditions to avoid LD degradation over all the analytical steps. LD instability will also influence the choice of the extraction technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, when DOPA is in excess, DA shows the wind-up and becomes uncontrollably high. The resulting high DA and DOPA levels can lead to increased and unfavorable oxidative stress by reactions with MAO/ROS leading to cell toxicity and neuropsychiatric disorders [ 30 , 45 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can cause serious side effects, such as dyskinesia [ 6 ]. It accelerates PD progression by inducing neuronal cell death through self-oxidation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%